Pengaruh Kualitas Pelayanan dan Kinerja Karyawan Terhadap Kepuasan Anggota KSPPS Fastabiq Khoiro Ummah Cabang Tambakromo - Sabila Vitra Meliyana; Amelia Anwar (Jurnal Manajemen Riset Inovasi, 2024)
KSPPS Fastabiq Khoiro Ummah Tambakromo branch is one of the KSPPS Fastabiq Khoiro Ummah branch offices located in Tambakromo district, Pati district. The aim of this research is to find out whether the variables of service quality and employee performance affect the satisfaction of members of the KPPS Fastabiq Khoiro Ummah Tambakromo branch. The method used is associative because it aims to determine the cause and effect of two or more variables. The sample was obtained from 100 respondents, savings members of the KSPPS Fastabiq Khoiro Ummah, Tambakromo Branch. The questionnaire method is the sampling technique used. Data is processed using reliability tests, validity, multiple liner regression tests, simultaneous tests. From the results of statistical tests there is a positive and significant influence simultaneously on the variables of service quality and employee performance on KSPPS member satisfaction. Fastabiq Khoiro Ummah Tambakromo branch is proven by an Fcount value of 133,016 and a significance level of 0.000 which is smaller than the significance level of 0.05, because Fcount is greater than Ftable which is 2.36. So it can be decided that the hypothesis is accepted which states that there is a significant influence and simultaneous between service quality and employee performance on member satisfaction of KSPPS Fastabiq Khoiro Ummah Tambakromo branch.